'I would rather go on being underdeveloped.' Rereading and recontextualising Edmundo Desnoes's 1965 novel Memorias del subdesarrollo. (1st December 2020) - Rowlandson, William
Abstract : This article follows two lines of inquiry. First, it provides a rereading of the novel Memorias del subdesarrollo (Desnoes 1965), suggesting that the protagonist, Sergio, is affected by the threat of nuclear war throughout the novel and that this fear dominates the text from the outset, and not just the novel's ending during the Missile Crisis of October 1962. It argues that Sergio's state of anxiety and inertia derive as much from this fear as from his intellectual detachment and problematic relationship with the Cuban Revolution, where critical attention has tended to focus. This rereading gives texture to Sergio's inaction and nihilism, revealing a coherent response of an individual to the threat of catastrophe. Secondly, this article sets this rereading against a new context of catastrophe: that of climate change, ecosystem collapse and species extinction. In this context an overlooked revolutionary fervour is detected in Sergio that provides a reading of hope in the narrative that, when read analogously against the present, may reflect a sense of hope against calamity.